Pengaruh Religiusitas, Kecerdasan Emosional, Kecerdasan Intelektual, Idealisme dan Status Ekonomi Terhadap Persepsi Etis Mahasiswa Akuntansi - Rozikin, Khoirur; Susilowati, Endah (Jurnal Etnik: Ekonomi-Teknik, 2023)
The purpose of this research was to test and prove the effect of reli giosity, emotional intelligence, intellectual intelligence, idealism and economic status on ethical perceptions of accounting students. The data used in this study is quantitative data. This research uses a data collection method, namely the questionnaire method. The questionnaire in this study will be given to respondents, namely UPN "Veteran" East Java accounting students class of 2019 who will be used as samples in this study. The data analysis technique used in this study is Partial Least Squares (PLS) with the help of WarpPLS 7.0 software. The results of this study indicate that religiosity contributes to ethical perceptions of accounting students. Emotional intelligence does not contribute to ethical perceptions of accounting students. Intellectual intelligence contributes to the ethical perceptions of accounting students. Idealism does not contribute to accounting students' ethical perceptions. Economic status contributes to ethical perceptions of accounting students.